Islam - Purwanto, Guntur Dwi; Shobirin; Chakim, Sulkhan (State Islamic Institute of Madura, 2021)
This research is a type of phenomenological research aimed at describing the position and role of the Darussalam pesantren as a medium for creating a positive image of SMK Darussalam Karangpucung Cilacap. The data in this study were collected using interview, observation and documentation techniques. After the data was collected, data analysis was carried out using the data analysis technique of the Miles and Huberman model consisting of data reduction, data presentation, and verification. The results showed that there were five roles played by Darussalam pesantren when carrying out its function as a social media for SMK Darussalam which was used to create a positive image of SMK. First, pesantren Darussalam was involved in implementing habituation activities at SMK. Second, the pesantren Darussalam has a role to produce alumni of SMK Darussalam who have the ability to preach in the community. Third, the Darussalam pesantren is believed to be the organizer of religious activities at SMK Darussalam. Fourth, the Darussalam pesantren was involved by the SMK in activities that were attended by the student's guardians. Fifth, the Darussalam pesantren was given facilities by the SMK to organize religious activities for the communities around the SMK. The five roles of pesantren as media have been successfully played so as to create a positive image of SMK Darussalam in the eyes of the public. The implication of creating a positive image is that there is always an increase in the acquisition of the number of new students at SMK Darussalam. The main factor that supports the success of the pesantren is due to the harmonious relationship between the pesantren and SMK and the community. This has shown a relationship between Islam, the media and society.